Методи управління прозорістю межі в неоднорідних пружних хвилеводах - Городецька, Наталія Сергіївна; Старовойт, Інна Валеріївна; Щербак, Тетяна Миколаївна (Стильна типографія, 2023)
Робота присвячена розробці методів керування ефективністю передачі енергії в складеному пружному хвилеводі. На основі аналізу розсіяного поля на межі ступінчатого хвилеводу, утвореного жорстким контактом двох півшарів з однаковими механічними характеристиками, але різної товщини, встановлено основні фактори, які впливають на прозорість межі розділу. Розглядалися гармонічні коливання, породжені розсіянням першої нормальної хвилі, що поширювалась з нескінченності у вужчому півшарі. Математичні труднощі поставленої граничної задачі обумовлені наявністю степеневої особливості по напруженням в точці зміни граничних умов на межі двох півшарів. Розв’язок будується методом суперпозиції, який дозволяє врахувати локальну особливість через асимптотичні особливості невідомих. Критерієм якості отриманого розв’язку був контроль точності виконання умов спряження на межі двох півшарів. Основна увага в роботі зосереджена на встановленні умов зміни прозорості межі в залежності від частот, симетрії коливань і співвідношення товщин півшарів. В роботі було показано, що як для симетричних, так і для антисиметричних коливань ступінчатого хвилеводу існують частотні діапазони, в яких прозорість межі суттєво змінюється. Для обох видів симетрії в діапазоні частот до критичної частоти для третьої поширюваної нормальної хвилі існує два частотних діапазони, в яких прозорість межі досить різко зростає. Частоти, на яких спостерігаються локальні максимуми енергії у відбитому полі, для симетричних і антисиметричних коливань різні. Для симетричних коливань перший максимум енергії у відбитому полі спостерігається на частоті, коли в обох півшарах може поширюватись тільки одна хвиля. Цей ефект обумовлений збільшенням ролі неоднорідних хвиль у пройденому полі. Другий максимум енергії у відбитому полі обумовлений трансформацією енергії падаючої хвилі в поширюванні хвилі вищих порядків. При антисиметричних коливаннях обидва максимуми обумовлені енергетичними особливостями поширюваних хвиль вищих порядків. Добротність резонансу енергії у відбитому полі виявилась також значно залежною від симетрії коливань. Встановлені особливості розсіяного поля дозволяють розробляти рекомендації щодо управління прозорістю межі в ступінчатому хвилеводі.

The work is devoted to the development of methods for controlling the efficiency of energy transfer in a composite elastic waveguide. Based on the analysis of the scattered field at the boundary of the stepped waveguide, formed by the rigid contact of two half-layers with the same mechanical characteristics, but with the different thicknesses, the main factors that affect the transparency of the interface were established. Harmonic oscillations generated by the first normal wave propagating from infinity in the narrower half-layer were considered. Mathematical difficulties of the posed boundary problem are due to the presence of a local singularity in the stresses at the point of change of the boundary conditions at the boundary of the two hemispheres. The solution is built by the superposition method, which allows taking into account the local singularity due to the asymptotic features of the unknowns. The quality criterion of the obtained solution was the control of the accuracy of the fulfillment of the conjugation conditions at the boundary of the two half-layers. The main attention in the work is focused on establishing the conditions for changing the transparency of the boundary depending on the frequencies, the symmetry of the oscillations, and the ratio of the half-layer widths. It was shown in the work that for both symmetric and antisymmetric oscillations of a stepped waveguide, there are frequency ranges in which the transparency of the boundary changes significantly. For both types of symmetry, in the frequency range up to the critical frequency for the third propagating normal wave, there are two frequency ranges in which the transparency of the boundary increases rather sharply. The frequencies at which local energy maxima are observed in the reflected field are different for symmetric and antisymmetric oscillations. For symmetric oscillations, the first energy maximum in the reflected field is observed at the frequency when only one wave can propagate in both half-layers. This effect is due to the increase in the role of inhomogeneous waves in the transmitted field. The second energy maximum in the reflected field is due to the transformation of the energy of the incident wave into propagating waves of higher orders. In the case of antisymmetric oscillations, both maxima are due to the energy features of propagating waves of higher orders. The quality of energy resonance in the reflected field depends significantly on the symmetry of the oscillations. The established features of the scattered field make it possible to develop recommendations for controlling the transparency of the boundary in a stepped waveguide.
Methods of controlling boundary transparency in non-homogenous elastic waveguides
Keywords: пружні хвилі; хвилевод; прозорість межі розділу; енергетичний аналіз; метод суперпозиції; асимптотичні особливості невідомих; добротність резонансу; elastic waves; interface transparency; energy analysis; superposition method; asymptotic properties of unknowns; resonance quality factor